Highly sensitive live-cell imaging-based cytotoxicity assay enables functional validation of rare epitope-specific CTLs - Wellach, Kathrin; Riemer, Angelika (Frontiers in immunology, 2025)
Many immunotherapeutic approaches aim to induce epitope-specific T-cell cytotoxicity. However, the identification—and especially the functional validation—of suitable epitopes by in vitro cytotoxicity assays can be challenging, particularly when the number of available epitope-specific cytotoxic T cells (CTLs) is limited. Here, we present a highly sensitive image-based cytotoxicity assay that allows the functional analysis of rare epitope-specific T cells. The live-cell imaging-based setup combines transient red labeling of target cells with a green caspase 3/7 probe, allowing reliable measurement of the fraction of apoptotic target cells. Time-course analysis enables the monitoring of subtle differences. This highly flexible assay can be applied to assess the killing of either target cells with endogenous epitope presentation or those artificially loaded with the epitope of interest. Analysis of assay sensitivity demonstrated that cytotoxicity mediated by as few as 0.1% epitope-specific CTLs in a T-cell culture can still be detected. The epitope-specificity of the assay was additionally validated by specific upregulation of PD-1 and LAG-3 on epitope-specific T cells, as well as the epitope-specific induction of interferon-γ release. Finally, the assay was successfully applied to functionally validate human papillomavirus (HPV)16 epitopes, by detecting epitope-specific killing of established patient-derived tumor cell lines by rare T-cell populations expanded from peripheral blood. Overall, this cytotoxicity assay setup provides a straightforward approach to assess the cytotoxic capacity of rare epitope-specific T cells and enables the analysis of T-cell responses against endogenously presented epitopes.